Memory as Perception of the Past: Compressed Time inMind and Brain. Issue 2 (February 2018) - Howard, Marc W.
Abstract : In the visual system retinal space is compressed such that acuity decreases further from the fovea. Different forms of memory may rely on a compressed representation of time, manifested as decreased accuracy for events that happened further in the past. Neurophysiologically, "time cells" show receptive fields in time. Analogous to the compression of visual space, time cells show less acuity for events further in the past. Behavioral evidence suggests memory can be accessed by scanning a compressed temporal representation, analogous to visual search. This suggests a common computational language for visual attention and memory retrieval. In this view, time functions like a scaffolding that organizes memories in much the same way that retinal space functions like a scaffolding for visual perception. Trends: The brain contains time cells in many regions that code for the time since a stimulus was encountered. Time cells show compression analogous to the compression of retinal space in visual perception. In short-term memory, and perhaps long-term memory, memory retrieval may utilize scanning of a temporal representation, analogous to visual scanning. In memory the recency effect – a decrease in "memory acuity" with the passage of time – parallels the decrease in acuity with eccentricity in vision. In memory the contiguity effect – a boost in "memory acuity" for stimuli near in time to a remembered event – is accompanied by a neural jump back in time. This is analogous to the boost in acuity that comes from changing fixation in vision.